Educators’ Strategic Roles in the Merdeka Curriculum and Their Impact on Students’ Interest in Learning Arabic - Rahma Aisha Nabila; Musli Musli; Mustar Mustar; Dina Chabib Uluum; Mursyid Mursyid; Fitri Nurul'ain Nordin (Alsina : Journal of Arabic Studies, 2026)
This study analyzes the strategic roles of teachers in implementing the Merdeka Curriculum and their contribution to developing students’ interest in learning Arabic at MTs Nurul Iman, Jambi City. A qualitative case study approach was employed, with data collected through interviews, questionnaires, classroom observations, and documentation involving 16 eighth-grade students and one Arabic teacher. Data analysis integrated Teacher Role Theory, Pedagogical Content Knowledge, and Interest Development Theory. The findings show that teachers effectively enacted their roles as facilitators, motivators, learning designers, role models, and assessors providing feedback. These roles contributed to triggering situational interest, maintaining student engagement, and fostering the development of individual interest in Arabic learning. In this context, students demonstrated high and sustained interest, reflected in active participation, awareness of the importance of Arabic, and willingness to engage in independent learning. However, the use of digital-based learning media remains suboptimal due to limited facilities and infrastructure. These findings highlight that successful implementation of the Merdeka Curriculum depends on the synergy between teachers’ competencies and institutional support.